2015
DOI: 10.1038/nrg3963
|View full text |Cite
|
Sign up to set email alerts
|

Augmented genetic decoding: global, local and temporal alterations of decoding processes and codon meaning

Abstract: The non-universality of the genetic code is now widely appreciated. Codes differ between organisms, and certain genes are known to alter the decoding rules in a site-specific manner. Recently discovered examples of decoding plasticity are particularly spectacular. These examples include organisms and organelles with disruptions of triplet continuity during the translation of many genes, viruses that alter the entire genetic code of their hosts and organisms that adjust their genetic code in response to changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 188 publications
(182 reference statements)
2
90
0
3
Order By: Relevance
“…ORF-situated G4s are reported to act as roadblock for elongating ribosomes 153; 154 . RNA G4s also stimulate ribosomal frameshifting 155 , the recoding event when ribosomes are forced to move backward or forward leading to alternative ORF on the same mRNA 156 . In contrast, poorly studied RGG domain-containing RBP Aven recognizes ORF-situated G4s in its mRNA targets to stimulate translation 157 .…”
Section: Proposed Functions Of Rna G-quadruplexesmentioning
confidence: 99%
“…ORF-situated G4s are reported to act as roadblock for elongating ribosomes 153; 154 . RNA G4s also stimulate ribosomal frameshifting 155 , the recoding event when ribosomes are forced to move backward or forward leading to alternative ORF on the same mRNA 156 . In contrast, poorly studied RGG domain-containing RBP Aven recognizes ORF-situated G4s in its mRNA targets to stimulate translation 157 .…”
Section: Proposed Functions Of Rna G-quadruplexesmentioning
confidence: 99%
“…Subsequent studies defined some such cues, generally identified in an ad hoc manner or using reporter constructs, that were found to contribute to start and stop codon recognition beyond the initial simple rules put forth by the canonical translation model (Figure 1). A broad set of elegant studies thus defined global and specialized translation mechanisms and have also revealed gaps in our understanding of decoding rules and have suggested a greater role for context than is explained by standard translation rules (reviewed in (Baranov et al, 2015; Grosjean and Westhof, 2016)). Systematic approaches to define the degree to which codon context influences translation, however, have long been limited by available experimental and computational tools.…”
Section: The Canonical Model For Translationmentioning
confidence: 99%
“…Their translation results in a protein with an N-terminal extension of the canonical ORF-encoded protein product, rather than the short, possibly unstable peptide products expected to result from uORF translation (Figure 2B;(Brar et al, 2012; Fields et al, 2015; Ingolia et al, 2011; Ivanov et al, 2011; Menschaert et al, 2013)). The context cues leading to these cases of alternative initiation remain undefined and are likely to be similar to those seen for uORFs, but their biological significance is clearly different, as these translation initiation events result in extensions to proteins that may affect their properties, including localization (Baranov et al, 2015; Touriol et al, 2003). …”
Section: Initiation: Context Can Influence Start Site Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bypassing is a recoding event that overrules the collinearity of mRNA and protein sequence in gene expression ( 1 ). Although these events were thought to be extremely rare for a long time, recent work has identified multiple ribosome bypassing elements in yeast mitochondria ( 2 ).…”
Section: Introductionmentioning
confidence: 99%